Response of plants used in cover crop mix to Meloidogyne enterolobii, Meloidogyne incognita and Pratylenchus brachyurus - Lopes, Ana Paula Mendes [UNESP]; Pereira, Alana Emanoele [UNESP]; Baquião, Eunice Maria [UNESP]; Amorin, Deucleiton Jardim [UNESP]; Wilcken, Silvia Renata Siciliano [UNESP] (FapUNIFESP (SciELO), 2023)
Cover crop species have been used in mixes in order to improve soil conditions; however, it is important to evaluate the relationship of the employed cultivars with phytonematodes to identify those that do not multiply the pathogens in the cultivated area. This study aimed to assess the response of 11 plant species used in cover crop mix to Meloidogyne enterolobii, M. incognita and Pratylenchus brachyurus. Six experiments were conducted in a greenhouse, using a completely randomized design, with five replications. BMX Potência RR soybean and Santa Clara tomato were used as controls. In at least one of the experiments, IPR 91 Baili buckwheat was susceptible (reproduction factor-RF ≥ 1) to M. enterolobii, M. incognita and P. brachyurus. Common white lupin, URS Altiva white oat, Iapar 61 (Ibiporã) black oat and Embrapa 139 (Neblina) black oat were susceptible to M. enterolobii and M. incognita and resistant (RF < 1) and/or immune (RF = 0) to P. brachyurus. IPR 89 rye and IPR 116 radish were found susceptible to M. incognita and P. brachyurus and resistant to M. enterolobii. BRS 1501 millet and Embrapa 29 (Garoa) black oat were susceptible to M. incognita and resistant/immune to M. enterolobii and P. brachyurus. Brachiaria ruziziensis was considered resistant to M. enterolobii and M. incognita and susceptible to P. brachyurus. URS Corona white oat was the only cover crop considered to be resistant and/or immune to all the nematode species evaluated.
Reação de espécies vegetais utilizadas em mix de plantas de cobertura a Meloidogyne enterolobii, Meloidogyne incognita e Pratylenchus brachyurus
Keywords: crop rotation; green manure; lesion nematode; Root-knot nematode